Teaching at The Right Level Approach with the Problem Based Learning Model Effect on Physics Problem Solving Ability - Nozia Ovratami; Rosane Medriati; Irwan Koto (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
Physics lessons are among the most interesting because they relate to actual events. Physics learning requires an independent learning process that equips students with problem-solving skills. This study examines how the Problem-based Learning (PBL) model and the Teaching at the Right Level (TaRL) strategy affect the resolution of physics issues involving momentum and impulse topics. There are 375 grade XI students participating in a quasi-experiment with a non-equivalent control group design. The TaRL technique and the PBL model had a substantial impact on physics problem-solving; there is a significant influence on students' problem-solving abilities and the magnitude of the influence, according to the results of the independent sample t-test, which had a significance value (Sig. 2-tailed) of 0.001, which is less than 0.05. Cohen's d = 1.08 (high) and the N-gain score was 0.61 (moderate) for the TaRL method and PBL model, respectively.